2012
DOI: 10.7783/kjmcs.2012.20.1.008
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effect of Chaenomeles sinensis Fruit on Amyloid β Protein (25-35)-Induced Neurotoxicity in Cultured Neurons and Memory Impairment in Mice

Abstract: : The present study investigated an ethanol extract of Chaenomeles sinensis fruit (CSF) for possible neuroprotective effects on neurotoxicity induced by amyloid β protein (Aβ) (25-35) in cultured rat cortical neurons and also for antidementia activity in mice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(13 citation statements)
references
References 36 publications
1
12
0
Order By: Relevance
“…Schwabach, Germany) to yield an ethanol extract (ACG, 55 g), which was then stored at room temperature until required. Aβ (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35) was purchased from Bachem (Bubendorf, Switzerland). Acetylthiocholine iodide and 5,5'-dithiobis-2nitrobenzoic acid (DTNB) were purchased from Sigma Chemical (St. Louis, MO, USA).…”
Section: Plant Materials and Extraction And Reagentsmentioning
confidence: 99%
See 3 more Smart Citations
“…Schwabach, Germany) to yield an ethanol extract (ACG, 55 g), which was then stored at room temperature until required. Aβ (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35) was purchased from Bachem (Bubendorf, Switzerland). Acetylthiocholine iodide and 5,5'-dithiobis-2nitrobenzoic acid (DTNB) were purchased from Sigma Chemical (St. Louis, MO, USA).…”
Section: Plant Materials and Extraction And Reagentsmentioning
confidence: 99%
“…Induction of memory impairment in mice and administration of ACG Memory impairment was induced by i.c.v. injection of 15 nmol of the aggregated form of Aβ (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35), as previously described [2]. ACG was administered orally 30 min before Aβ (25-35) injection on experimental day 1 (ED1) and then further administered daily for 7 days (to ED8).…”
Section: Experimental Animalsmentioning
confidence: 99%
See 2 more Smart Citations
“…There has been much effort to develop beneficial agents from medicinal plants with free radical scavenging and anti-inflammatory properties to achieve neuroprotection in our laboratory (Jung et al, 2012;Kim et al, 2011). In our previous studies, aerial parts, leaves and stems, of Vitis amurensis and Aralia cordata were demonstrated to show neuroprotective effect against Aβ (25-35)-induced neurotoxicity in in vivo and in vitro (Cho et al, 2009;Jeong et al, 2010).…”
Section: Introductionmentioning
confidence: 99%